Pengaruh Penambahan Ekstrak Jamur Laut Sebagai Pakan Aditif Dalam Ransum Terhadap Bobot Karkas Ayam Lokal - Rajonsen Purba; Nurhayati; Nelwida (Jurnal Ilmu Peternakan Indonesia, 2026)
This study aims to determine the effect of adding marine mushroom extract as a feed additive in rations on local chicken carcasses. The design used was a Completely Randomized Design (CRD) consisting of 5 treatments and 4 replications. The treatments used in this study were P0 = Basic Ration (control), P1 = P0 + 1 ml sea mushroom / kg, P2 = P0 + 2 ml sea mushroom / kg, P3 = P0 + 3 ml sea mushroom / kg and P4 = P0 + 4 ml sea mushroom / kg. The variables observed included feed consumption, slaughter weight, absolute carcass weight and relative carcass weight. The results of the analysis of variance showed that the addition of sea mushroom extract as a feed additive in the ration had no significant effect (P>0.05) on feed consumption, slaughter weight, absolute carcass weight and relative carcass weight. Based on the results of this study, it can be concluded that the addition of sea mushroom extract as a feed additive in the ration added up to 4 ml sea mushroom / kg ration has not been able to increase carcass weight in native chickens.